Foreign ownership and productivity: New evidence from the service sector and the R&D lab - Rachel Griffith; Stephen Redding; Helen Simpson (Institute for Fiscal Studies (IFS), 2004)
This paper examines the relationship between foreign ownership and productivity, paying particular attention to two issues neglected in the existing literature Ö the role of multinationals in service sectors and the importance of R&D activity conducted by foreign multinationals. We review existing theoretical and empirical work, which largely focuses on manufacturing, before presenting new evidence using establishmentlevel data on production, service and R&D activity for the United Kingdom. We find that multinationals play an important role in service sectors and that entry of foreign multinationals by takeover is more prevalent than greenfield investment. We find that British multinationals have lower levels of labour productivity than foreign multinationals, but the difference is less stark in the service sector than in the production sector, and that British multinationals have lower levels of investment and intermediate use per employee. We also find that foreign-owned multinationals conduct a substantial amount of UK R&D. We discuss the implications of these and other findings for the policy debate on incentives to influence multinational firms' location choices.
Keywords: F23; O47; L60; L80; 330; Foreign Investment; Productivity; Knowledge Spillovers; Eigentümerstruktur; Direktinvestition; Multinationales Unternehmen; Industrielle Forschung; Produktivität; Dienstleistungssektor; Großbritannien